Legal Assurance: A Comparative Study of the Good Faith Doctrine in Australia and Indonesia - Muhammad Jibril; Talitha Amanda Ekadhani (Muhammadiyah University Press, 2021)
Purpose: This study aims to analyze and compare the legal assurance of the good faith doctrine in Indonesia and Australia by examining the doctrine's existence in each jurisdiction.Methodology: This study used a normative legal research method through a case approach, both in Australia and in Indonesia.Results: The results of this study show that good faith does not have a definite definition in either Indonesia or Australia, but the existence of good faith is clearer in Indonesia than in Australia.Applications of the study: This study examines the comparison of good faith in Australia and Indonesia both in terms of definition and position in contract law. Furthermore, it also provides an overview of legal assurance in two different legal systems.Novelty/Originality: This study compares the regulation of the doctrine of good faith in Indonesia and Australia using a case approach (jurisprudence) which is still rarely used in Indonesia.